JUDICIAL DECISION FOR A WITNESS PROTECTION IN INDIA - Shrivastava, Geeta; Tulika; Rani, Mamta (International Journal of Psychosocial Rehabilitation, 2020)
In a criminal case, there is a lot of evidence, whether it comes from witnesses or from other sources. Many countries that are well-developed have laws that protect witnesses, but in India, there is no law that protects witnesses. People are in a bad situation because there isn't enough law to protect them. India's courts have played a positive role in protecting witnesses in many cases. This led to a lot of support for setting up Witness Protection Programs in the country. Rule of law is important when witnesses can give evidence in court without fear of intimidation or reprisal.